Etika, CSR, dan Strategi Menjaga Keberlanjutan Lingkungan Sekitar: Strategi Resposibilitas sosial perusahaan terhadap Kelanggengan Lingkungan Sekitar - Khairunnisa Hanum; Yasmi Fazrah (Masyarakat Ekonomi Syariah Bogor, 2023)
The topic of corporate ethics must be brought up in all transactional actions. The expansion of human civilization and the fiercer competition have led to many entrepreneurs finding new means to accomplish their objectives. Additionally, business must be conducted. Companies utilize corporate social responsibility (CSR) as a concept and a strategy to address the demands and interests of their stakeholders. CSR was first developed at a time when considering a company's long-term viability was more significant than just its profitability. However, in practice, many businesses are implementing Corporate Social Responsibility (CSR) programs that serve the love of human interactions by engaging in humanitarian or philanthropic endeavors. As a big business using CSR as a sort of activity to get the. As a huge corporation, you may be using CSR as a kind of activity to ask the government to certify that your business operations are legitimate. The approach utilized for this type of study is library research, which is a way of gathering data and information using resources from the library, such as old books, books, journals, periodicals, and other library materials.